2021
DOI: 10.3390/rs13081535
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Forest Canopy Height in Northern China by Synergizing ICESat-2 with Sentinel-2 Using a Stacking Algorithm

Abstract: The forest canopy height (FCH) plays a critical role in forest quality evaluation and resource management. The accurate and rapid estimation and mapping of the regional forest canopy height is crucial for understanding vegetation growth processes and the internal structure of the ecosystem. A stacking algorithm consisting of multiple linear regression (MLR), support vector machine (SVM), k-nearest neighbor (kNN), and random forest (RF) was used in this paper and demonstrated optimal performance in predicting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 63 publications
5
33
0
Order By: Relevance
“…In accordance with previous studies, the MSI was more useful than the SAR and DEM for the LAI estimation, providing a wider range of the predicted LAI values. This is likely because the MSI data consist of optical sensor readings; spectral indices from the narrow-band, red-edge, and SWIR spectral regions are sensitive to green vegetation and are useful for retrieving forest phenology, physiology, and structure [13,23,28]. However, the MSI suffers from data saturation due to the forest canopy's shading of solar radiation in thick forest zones, which causes the MSI to a record horizontal vegetation structure more effectively than vertical biophysical characteristics [49].…”
Section: Roles Of Sentinel-1 and 2 And Alos-dem In Forest Lai Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…In accordance with previous studies, the MSI was more useful than the SAR and DEM for the LAI estimation, providing a wider range of the predicted LAI values. This is likely because the MSI data consist of optical sensor readings; spectral indices from the narrow-band, red-edge, and SWIR spectral regions are sensitive to green vegetation and are useful for retrieving forest phenology, physiology, and structure [13,23,28]. However, the MSI suffers from data saturation due to the forest canopy's shading of solar radiation in thick forest zones, which causes the MSI to a record horizontal vegetation structure more effectively than vertical biophysical characteristics [49].…”
Section: Roles Of Sentinel-1 and 2 And Alos-dem In Forest Lai Estimationmentioning
confidence: 99%
“…We also found that the NBL significantly affected the SL model performance. However, many previous prediction studies [25,[27][28][29][30] did not attempt to optimize the NBL when generating SL models. In this work, the best NBL for estimating the LAI was determined through a comparative analysis of SL models (Figure 4), which revealed that the use of too many or too few base learners reduced the accuracy of SL models.…”
Section: Usefulness Of Stacking Learning Models For Forest Lai Quanti...mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the NASA's Geoscience Laser Altimeter System (GLAS) was used to estimate fire fuel models (e.g., Ashworth et al, 2010), canopy fuel properties for crown fire behavior (e.g., García et al, 2012), and canopy structure and fuel data (e.g., Peterson et al, 2013). The NASA's Advanced Topographic Laser Altimeter System (ATLAS) instrument, launched in 2018, can also be used for vegetation characterization (Narine et al, 2020), although few studies have been conducted to date (e.g., Jiang et al, 2021;Lin et al, 2020;Narine et al, 2019) and none of them on the estimation of forest fuels. However, it should be noted that both GLAS and ATLAS systems were not initially optimized for vegetation and forest structure characterization (Leite et al, 2022, Potapov et al, 2021.…”
Section: Introductionmentioning
confidence: 99%
“…The airborne laser radar can obtain very high inversion accuracy, but only on a small scale. Spaceborne lidar can cover the entire world, but can only provide sampling spot data [14]. At present, ICESat-1 (ice, cloud, and land Elevation Satellite 1), ICESat-2 (ice, cloud, and land Elevation Satellite 2) and GEDI (Global Ecosystem Dynamics Investigation) are the main spaceborne lidars for forest parameter structure measurement.…”
Section: Introductionmentioning
confidence: 99%